PERAN PEREMPUAN PENGELOLA USAHA KECIL DALAM KEHIDUPAN EKONOMI KELUARGA DI KELURAHAN WENANG SELATAN KOTA MANADO - Oroh, Sandra Eunike (HOLISTIK, Journal Of Social and Culture, 2013)
The women managers of small businesses in the Sub District of south Wenang very significant in supporting the economic life of the family. It can be seen from the two roles are performed simultaneously in their household: the role of domenstic and public roles. Domenstic role as a housewife as cooking, child care, washing, etc, while the women in the family also had to run a public role breadwinner by working with open and manage a small business in their home to supplement the family income. Beside that, they also have the ability to manage finances drawing this sufficient financial businesses and families, so that they can continue to run the business and family needs can be overcome. While the motivation of women to work as managing a small business is the economic factor that is less households, empowering abilities and skills their spare time in the family.Keywords : woman, business, manage